Analisa Harmonisa dan Faktor Daya Peralatan Listrik Rumah Tangga Pada Sistem Tegangan Rendah 220 V - Eva Magdalena Silalahi (G-Tech: Jurnal Teknologi Terapan, 2024)
Common domestic electrical equipment include air conditioners, televisions, fans, washing machines, refrigerators, rice cookers, irons, water heaters, computers, laptops, and others. TVs, PCs, and laptops are nonlinear electrical loads that generate harmonics with low power factors. This study intends to determine theTHDv and THDi of electrical equipment and compare them with the IEEE 519-2014 standard. The power factor relates to the PLN power factor standard of ≥0.85. The data analysis results demonstrate that this electrical equipment's THDv fulfills the norm. Nonlinear load electrical equipment is often made up of electronic components with a THDi of 118.36% to 216.42% and a power factor of 0.36 to 0.6. THDi and power factor vary, namely: THDi 7.60% to 22.73% and a power factor of 0.46 to 0.98. And linear load electrical equipment, THDi 1.07% to 2.10%, and power factor 0.98 to 1.0.